New Insights Into Heat Shock Protein 90 in the Pathogenesis of Pulmonary Arterial Hypertension - Hu, Liqing; Zhao, Rui; Liu, Qinglian; Li, Qianbin (Frontiers in Physiology, 2020)
Pulmonary arterial hypertension (PAH) is a multifactorial and progressive disorder. This disease is characterized by vasoconstriction and vascular remodeling, which results in increased pulmonary artery pressure and pulmonary vascular resistance. Although extensive studies have been carried out in order to understand the etiology, it is still unclear what intracellular factors contribute and integrate these pathological features. Heat shock protein 90 (Hsp90), an ubiquitous and essential molecular chaperone, is involved in the maturation of many proteins. An increasing number of studies have revealed direct connections between abnormal Hsp90 expression and cellular factors related to PAH, such as soluble guanylate cyclase and AMP-activated protein kinase. These studies suggest that the Hsp90 regulatory network is a major predictor of poor outcomes, providing novel insights into the pathogenesis of PAH. For the first time, this review summarizes the interplay between the Hsp90 dysregulation and different proteins involved in PAH development, shedding novel insights into the intrinsic pathogenesis and potentially novel therapeutic strategies for this devastating disease.